HvPap-1 C1A Protease and HvCPI-2 Cystatin Contribute to Barley Grain Filling and Germination. Issue 4 (24th February 2016) - Diaz-Mendoza, Mercedes; Dominguez-Figueroa, Jose D.; Velasco-Arroyo, Blanca; Cambra, Ines; Gonzalez-Melendi, Pablo; Lopez-Gonzalvez, Angeles; Garcia, Antonia; Hensel, Goetz; Kumlehn, Jochen; Diaz, Isabel; Martinez, Manuel
Abstract : Over-expressing or silencing proteases or their inhibitors alter the metabolite composition of the grain and modify the germination process in barley Abstract: Proteolysis is an essential process throughout the mobilization of storage proteins in barley ( Hordeum vulgare ) grains during germination. It involves numerous types of enzymes, with C1A Cys proteases the most abundant key players. Manipulation of the proteolytic machinery is a potential way to enhance grain yield and quality, and it could influence the mobilization of storage compounds along germination. Transgenic barley plants silencing or over-expressing the cathepsin F-like HvPap-1 Cys protease show differential accumulation of storage molecules such as starch, proteins, and free amino acids in the grain. It is particularly striking that the HvPap-1 artificial microRNA lines phenotype show a drastic delay in the grain germination process. Alterations to the proteolytic activities in the over-expressing and knock-down grains associated with changes in the level of expression of several C1A peptidases were also detected. Similarly, down-regulating cystatin Icy-2, one of the proteinaceous inhibitors of the cathepsin F-like protease, also has important effects on grain filling. However, the ultimate physiological influence of manipulating a peptidase or an inhibitor cannot be always predicted, since the plant tries to compensate the modified proteolytic effects by modulating the expression of some other peptidases or their inhibitors.